Perioperative outcomes of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy in elderly women with epithelial ovarian cancer: analysis of a prospective registry. Issue 7 (July 2021) - Chambers, Laura M; Yao, Meng; Morton, Molly; Chichura, Anna; Costales, Anthony B; Horowitz, Max; Gruner, Morgan F; Rose, Peter G; Michener, Chad M; DeBernardo, Robert
ABSTRACT : Objective : To evaluate perioperative outcomes in elderly versus non‐elderly women with advanced or recurrent epithelial ovarian cancer undergoing surgery with hyperthermic intraperitoneal chemotherapy (HIPEC). Methods : A single‐institution prospective registry was analyzed for women with ovarian cancer who underwent surgery with HIPEC from January 2014 to December 2020. Elderly age was defined as ≥65 years at surgery. Complications were defined according to the Accordion scale. Univariate and multivariable analysis was used to compare progression‐free survival and overall survival. Results : Of 127 women who underwent surgery with HIPEC, 33.1% (n=42) were ≥65 and 17.3% (n=22) were ≥70 years old. The median age for non‐elderly and elderly patients were 55.7±8.3 versus 72.0±5.4 years, respectively (p<0.001). The majority of non‐elderly versus elderly patients underwent HIPEC at the time of interval cytoreductive surgery following neoadjuvant chemotherapy (52.9% vs 73.8%, p=0.024). There were no differences in moderate (15.3% vs 26.2%) or severe postoperative complications (10.6% vs 11.9%, p=0.08), acute kidney injury (7.1% vs 16.7%, p=0.12), and length of stay (5.0 vs 5.0 days, p=0.56) for non‐elderly versus elderly patients. With a median follow‐up of 20 months (95% CI 9.1 to 32.7 months), there was no difference in progression‐free survival (18.8 vs 15.7 months, p=0.75) or overall survival (61.6 months vs not estimable, p=0.72) for non‐elderly versus elderly patients. Comparing patients 65‐69 versus ≥70 years, progression‐free survival (33.0 vs 12.5 months, p=0.002) was significantly improved in patients aged 65‐69, without difference in overall survival (not estimable vs 36.0 months, p=0.91). On multivariable analysis, age ≥65 did not impact progression‐free survival (p=0.74). Conclusions : In this prospective registry of women with ovarian cancer, perioperative morbidity is not increased for non‐elderly versus elderly patients following surgery with HIPEC. While age should not exclude patients from surgery with HIPEC, additional research is needed regarding oncologic benefits in elderly women.